BS EN ISO/IEC 15067-3-51. Information technology. Home Electronic System (HES) application model. Part 51. Framework of a Protected On-Premises Narrow AI Engine for an Energy Management System using Energy Management Agents (EMAs) (17th July 2020) - British Standards Institution,
No abstract available